Retirement homes: Social participation and quality of life - Amiri, Elham (Electron Physician, 2017)
INTRODUCTION: Social participation is considered as a means of improving one’s quality of life, thus the study aimed at assessing the association between the quality of life and social participation in the elderly. METHODS: This cross-sectional study was conducted in 2016. The study population was selected from among the residents of a retirement home (an elderly residential home) in one of the Northwestern provinces of Iran, and the required data was collected via three questionnaires related to the demographic data, the specific quality of life for the elderly (LEIPAD), and the extent of social participation. Data was analyzed using mean, standard deviation, Spearman correlation coefficient, Mann-Whitney, Chi-square and Kruskal-Wallis test in SPSS software. RESULTS: The social participation level of the population under study was estimated as being appropriate (mean score: 3.81±0.32); whereas, the respondents’ quality of life was estimated as being relatively inappropriate (mean score: 2.78±0.41). The “art, sport and leisure activities” subscale showed a significant relationship with the subscales related to the total quality of life and those of “Physical Performance” (r=0.128, p=0.46), “depression and anxiety”(r=0.114, p=0.051), “sexual performance”(r=0.213, p=0.21), and “life satisfaction”(r=0.272, p=0.11); furthermore, there was a significant relationship between total social participation and “life satisfaction” and the subscales related to “depression and anxiety”(r=0.263, p=0.12). CONCLUSIONS: It seems that activities that involve the art, sport and leisure subscale of social participation can result in quality of life improvement for the elderly.